The influence of pH, polyethylene glycol and polyacrylic acid on the stability of stem bromelain - Letícia Celia de Lencastre Novaes; Angela Faustino Jozala; Priscila Gava Mazzola; Adalberto Pessoa Júnior (Universidade de São Paulo, 2014)
Enzyme stability is critical in biotechnology, pharmaceutical and cosmetic industries. Investigations on this subject have drawn attention because of its practical application. Bromelain is a thiol-endopeptidase, obtained from pineapple (Ananas comosus), known for its clinical and therapeutic applications, particularly to selective burn debridement and improvement of antibiotic action and anti-inflammatory activities. To date, the use of bromelain in pharmacological or industrial applications is limited, due to commercial availability, costs, and sensitivity to pH and temperature. Therefore, a better understanding of enzyme stability would be of great interest. The aim of this study was to evaluate bromelain activity and stability in several pH (2.0 to 8.0) and in polyethylene glycol and polyacrylic acid solutions. We observed that bromelain was able to maintain its stability at pH 5.0 for the temperatures studied. PEG solutions increased bromelain stability, but PAA solutions had the opposite effect.